Kebijakan Pelayanan Publik Pemerintah Daerah di Era Disrupsi - Novida Anggraini; Taufiqurokhman Taufiqurokhman; Disson Muhammad Fauzi; Watriningsih Watriningsih (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Openness in the development of policy making is a must in local governments to carry out good public services in accordance with Good Governance. The purpose of this research is to see the development of the concept of administration to public administration in implementing local government decisions. So that the openness of a policy by involving community participation results in satisfaction with public services for the wider community. The research methodology uses a qualitative descriptive approach to the problem of openness to policy developments in public services by local governments. As a result, the community can enjoy and feel the involvement of participation in a decision-making process carried out by the local government. The legal basis for making public policy implementation by the government is the principle of decentralization, namely the granting of regional autonomy to local governments. As guaranteed in Law No. 32/2004 article 14 on mandatory local government affairs